Prediction of Endurance Performance and Repeated Sprint Ability Based on Critical Velocity in Soccer Players Depending on their Playing Position - Rostami, Milad; Alizadeh, Rostam; Rezaeinezhad, Najmeh (Health Nexus, 2025)
Tests and regular monitoring of the athlete’s’ performance is an important aspect of a successful training program. However, the methods of conducting tests are challenging, particularly in team sports. The present study is an attempt to predict endurance performance and repeated sprint ability based on critical velocity (CV) and anaerobic distance capacity (ADC) in soccer players according to their playing position. The current research used a causal ex post facto design. 60 players from the same team (Ilam, Iran) participating in 3-5 regular practice sessions a week, with an age range of 16-20 years participated in this study as volunteers. They are divided in 6 playing positions (Fullback, Center Back, Defending/Holding Midfielder (CDM), Midfielder Offensive, Winger and Striker) presenting homogeneous level, experience, volume and intensity of training. Body composition, 400m and 1600m running tests and Running-Based Anaerobic Sprint Test (RAST) were measured. CV and ADC were measured using 400m and 1600m running time data. Linear regression test was used to predict the relationship between the variables and one-way analysis of variance (ANOVA) was used to determine the differences between the players in different positions. Results of the linear regression model showed that CV and ADC ha significantly impact maximum, minimum, average power, aerobic and anaerobic performance in irrespective of the playing position. Regardless of the game positional role. CV of Fullback had an effect on the minimum, average power and decremental index, and the ADC variable in the Center Back position had an effect on the minimum power. However, CV and ADC variables had a significant effect on the prediction of aerobic and anaerobic performance in all six game positions. The results of the one-way ANOVA statistical test showed that there was a significant difference between the different positions only in the deceleration index factor (p=0.015), and the results of the Bonferroni test showed that this difference was between the Midfielder Offensive and winger groups (p=0.012). This study has shown relevant information for coaching about the use of C.V and ADC in order to propose new keys and ways of planning training sessions.